2017
DOI: 10.1016/j.chemphys.2016.09.006
|View full text |Cite|
|
Sign up to set email alerts
|

Theoretical and experimental investigation of Electron Transfer Mediated Decay in ArKr clusters

Abstract: We investigate the electronic decay of an Ar 3s −1 vacancy in medium sized ArKr clusters. The only energetically accessible, radiationless decay mechanism is Electron Transfer Mediated Decay Three (ETMD3). Here, the argon vacancy is lled by an electron from one krypton atom, and the excess energy is transferred to a second krypton atom which consequently emits an electron. For the theoretical calculation of ETMD3 spectra, in a bottom-up approach, we study the dependence of the decay width on the geometry of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 72 publications
1
19
0
Order By: Relevance
“…For mixed rare gas systems, efficiencies of (or close to) 100%, within the experimental uncertainty, were also found for excited states that may decay by ICD and ETMD, or solely by ETMD. 223 , 283 …”
Section: Systems and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For mixed rare gas systems, efficiencies of (or close to) 100%, within the experimental uncertainty, were also found for excited states that may decay by ICD and ETMD, or solely by ETMD. 223 , 283 …”
Section: Systems and Applicationsmentioning
confidence: 99%
“…The theoretical formalism used for analysis of the NeAr ICD spectra ( Figure 31 ) was extended to also cover ETMD, and its application to the ArKr decay led to a good agreement with experiment. 283 …”
Section: Systems and Applicationsmentioning
confidence: 99%
“…1(a)]. Decay to Ne-Kr ++ states is often called the electron transfer mediated decay (ETMD) channel (see, e.g., [50,51]). In NeKr dimers, the direct population of these states via the ETMD process is suppressed by concurrent ICD.…”
Section: Theorymentioning
confidence: 99%
“…In the past years it was found that the related electron-transfer mediated decay process of three atoms depends on their exact constellation. 56 We assume the same for ICD. Therefore, we consider in this study systems of three binding sites with a two-dimensional continuum and a two-dimensional conformation space for their arrangement.…”
Section: Introductionmentioning
confidence: 99%